2020
DOI: 10.4049/jimmunol.2000164
|View full text |Cite
|
Sign up to set email alerts
|

LILRB1 Intron 1 Has a Polymorphic Regulatory Region That Enhances Transcription in NK Cells and Recruits YY1

Abstract: LILRB1 is a highly polymorphic receptor expressed by subsets of innate and adaptive immune cells associated with viral and autoimmune diseases and targeted by pathogens for immune evasion. LILRB1 expression on human NK cells is variegated, and the frequency of LILRB1 + cells differs among people. However, little is known about the processes and factors mediating LILRB1 transcription in NK cells. LILRB1 gene expression in lymphoid and myeloid cells arises from two distinct promoters that are separated by the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…Our results suggest a dose effect as more patients displaying a homozygous genotype were alloimmunised; these results, however, did not reach statistical significance, possibly as the study size was underpowered. Our results confirm the important level of diversity of this gene [39,45], as each patient displayed a unique haplotype. Both of these polymorphisms have previously been associated with lower expression on the NK cell surface [39,44,45], inflammation and immune disorders, and cancer outcomes [42,43].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results suggest a dose effect as more patients displaying a homozygous genotype were alloimmunised; these results, however, did not reach statistical significance, possibly as the study size was underpowered. Our results confirm the important level of diversity of this gene [39,45], as each patient displayed a unique haplotype. Both of these polymorphisms have previously been associated with lower expression on the NK cell surface [39,44,45], inflammation and immune disorders, and cancer outcomes [42,43].…”
Section: Discussionsupporting
confidence: 84%
“…The highest affinity of HLA-G is for the inhibitory receptors LILRB1 and LILRB2. Both receptors harbour immunoreceptor tyrosine-based inhibitory motifs (ITIMs), aiding the inhibition of intracellular signal transduction [38,39]. LILRB1 is expressed on several distinct types of immune cells, including monocytes, B cells, dendritic cells (DCs), subsets of effector and memory T cells, and 20-70% of NK cells [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanism of the LILRB1 polymorphism in human NK cells is unknown, the expression of LILRB1 on NK cells is linked to particular haplotypes and a polymorphic regulatory region. 42 The increase of LILRB1 + NK cells from certain patients with cancer was well documented. NK cells upregulated LILRB1 expression when cultured with cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the frequency of LILRB1 D1-D2 variants shows population difference and variants 1–3 represent the three most frequent LILRB1 D1-D2 variants in worldwide populations. Additionally, polymorphisms in the introns and UTRs were also examined in several studies (Kuroki et al 2005 ; Davidson et al 2010 ; Wiśniewski et al 2015 ; Yu et al 2020 ). However, we did not include the polymorphisms in the non-coding region in our study.…”
Section: Discussionmentioning
confidence: 99%